Fermented brown rice flour as functional food ingredient - Ilowefah, Muna; Chinma, Chiemela; Bakar, Jamilah; Mohd Ghazali, Hasanah; Syed Muhammad, Sharifah Kharidah; Makeri, Mohammad (MDPI, 2014)
As fermentation could reduce the negative effects of bran on final cereal products, the utilization of whole-cereal flour is recommended, such as brown rice flour as a functional food ingredient. Therefore, this study aimed to investigate the effect of fermented brown rice flour on white rice flour, white rice batter and its steamed bread qualities. Brown rice batter was fermented using commercial baker’s yeast (Eagle brand) according to the optimum conditions for moderate acidity (pH 5.5) to obtain fermented brown rice flour (FBRF). The FBRF was added to white rice flour at 0%, 10%, 20%, 30%, 40% and 50% levels to prepare steamed rice bread. Based on the sensory evaluation test, steamed rice bread containing 40% FBRF had the highest overall acceptability score. Thus, pasting properties of the composite rice flour, rheological properties of its batter, volume and texture properties of its steamed bread were determined. The results showed that peak viscosity of the rice flour containing 40% FBRF was significantly increased, whereas its breakdown, final viscosity and setback significantly decreased. Viscous, elastic and complex moduli of the batter having 40% FBRF were also significantly reduced. However, volume, specific volume, chewiness, resilience and cohesiveness of its steamed bread were significantly increased, while hardness and springiness significantly reduced in comparison to the control. These results established the effectiveness of yeast fermentation in reducing the detrimental effects of bran on the sensory properties of steamed white rice bread and encourage the usage of brown rice flour to enhance the quality of rice products.